Inovasi Instrumen Penilaian Autentik Maharah Istima' dengan Pendekatan Pragmatik dalam Buku Bahasa Arab Kelas VIII - Sarah Salsabila; R.Umi Baroroh; Andi Hazrah Nurhaliza ibrahim; Aufa Rahma (STIQ Amuntai, 2026)
This study aims to design an authentic assessment instrument for listening skills (maharah istima’) in learning Arabic for class VIII of Madrasah Tsanawiyah, using a pragmatic approach. Authentic assessment was chosen because it can fully describe students' abilities in understanding language as a real communication tool, not only as a symbolic system. Meanwhile, the pragmatic approach emphasizes the importance of context, speaker intention, and implicit meaning in oral communication. The research method used is library research combined with document analysis of Arabic books for class VIII published by the Ministry of Religious Affairs of the Republic of Indonesia. This study produces an assessment instrument model organized by each learning chapter, with multiple-choice, open-answer, and matching questions, all based on audio and real-world contexts. The main results of this instrument design indicate that students can be trained to understand implied meaning, respond contextually, and recognize intentions and emotions in oral communication. Assessment is no longer focused on literal memorization but on critical and applicable language skills. The main conclusion of this study is that integrating a pragmatic approach into authentic maharah istima' assessment can increase the relevance, depth of meaning, and functionality of Arabic language-learning evaluation. This model is expected to be an alternative evaluation that is more engaging, meaningful, and aligned with the demands of 21st-century skills. Therefore, further research should focus on experimentally testing the effectiveness of this instrument to validate its significant impact on students' pragmatic literacy.